Analisis Upaya Penerapan Pendidikan Karakter Dalam Memupuk Sikap Partiotik Cinta Tanah Air Dan Bela Negara Di Sekolah Dasar (International Forum of Researchers and Lecturers, 2023)
This study aims to identify character education of patriotic attitudes of loving the motherland and defending the country in elementary schools and showing phenomena that occur in the field regarding patriotic attitudes and defending the country, the responses of students and teachers to various character education activities, and the efforts made so that students gain knowledge about patriotic attitudes of love for the motherland and defending the country. This research is a research using a qualitative approach by looking for various theoretical descriptions, findings and other research materials obtained from reference materials to serve as the basis for activities. The research results show that the character of loving the motherland has been instilled since school days, one of which is with ceremonial activities in which there are many activities that will foster love for the motherland from each student such as flag raising, singing Indonesia Raya songs and various other national obligatory songs, reading texts pancasila, the mandate of the ceremony and even remembering the services of the heroes by praying and not forgetting to also use complete uniforms and attributes according to the rules that are included in the activities of loving the country. With the conclusion that instilling the character of loving the homeland is very necessary to start from elementary school so that it can be embedded in the memory of each student properly.